Village Financial Management Analysis (Case Studydesa Amplas Subdistrict Percut Sei Tuan) - Fina Afrillia Surbakti; Azahra Sani, Adinda Salwa; Nadeak, Paiman Eliazer; Ivanna, Julia (PT. Berlian Pustaka Indonesia, 2023)
The purpose of this study is to describe the analysis of income and expenditure management and village finances. The method used in this study is a qualitative descriptive method and the data source used is primary data obtained by in-depth interviews and observations with Amplas village. Along with economics development in Indonesia, the government issued a Village fund allocation program to improve community service facilities, in the form of meeting basic needs, strengthening village institutions and other activities needed by village communities by making decisions through deliberations. Village Fund Allocations are balancing funds received by districts/cities in the district/city regional Revenue and Expenditure Budget (APBD) after deducting the Special Allocation Funds. this research was conducted in Sandpaper village, Percut Sei Sir districts, Deli Serdang regency, North Sumatra province.